The identification of management potential - Jenk, Margaret Ruth (My University, 1991)
The study was undertaken in order to determine whether it would be possible to isolate certain competencies which could be used to identify individuals with management potential in a population of branch and area managers within a financial institution. The competencies selected for study were extracted from an extensive review of the relevant literature and were selected for both relevance and ease of measurement. The competencies were Locus of Control, Achievement Motivation, Cognitive skills and Interpersonal skills. The subjects were divided into two groups on the basis of a panel assessment by senior management of the organisation. The first group consisted of those individuals who were seen as having the potential for further advancement and the second of the balance. The relevant competencies were measured for both groups. It was found that age, time spent in current position, Control of Social relationships, a sub-factor of Locus of Control and Awareness of level and Personal Excellence, sub-factors of Achievement Motivation differentiated significantly between the two groups. In addition, Cognitive and Interpersonal skills differentiated strongly between the two groups. Contrary to expectations, subjects with potential were found to be significantly more externally controlled with respect to the factor Control of Social relationships. Possible reasons for this are explored. Finally, it was attempted to construct a predictive model for use in identifying management potential. The model met with limited success, but was significant in that it highlighted the inadequacies of the "country-club" method of assessment.
A RESEARCH REPORT SUBMITTED TO THE FACULTY OF BUSINESS ADMINISTRATION OF THE UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF MANAGEMENT (HUMAN RESOURCE MANAGEMENT)
Keywords: Executive ability -- South Africa.; Executive ability.